Historians and the trouble of defining aristocracy - Sarti, C (Winchester University Press, 2024)
This introduction to the special issue Defining Aristocracy eases the reader slowly into the various troubles historians have in defining aristocracy. It argues for embracing the fuzziness of the term, and building research from there. The introduction also gives an overview of the special issue, and a short summary of the articles. The trouble historians have of defining aristocracy is discussed and contextualised within the broader historiography, but, based on the four articles on eighteenth-century Geneva, modern Swedish historiography discussing early modern aristocracy, nineteenth-century Habsburg, and finally Tudor England, a way forward is offered. Despite the trouble of actually defining aristocracy, speaking about it, thinking about it, and trying to elucidate it is indeed meaningful and fruitful for research.